Brainstem Cavernous Malformations Management: Microsurgery vs. Radiosurgery, a Meta-Analysis - Fotakopoulos, George; Andrade-Barazarte, Hugo; Kivelev, Juri; Tjahjadi, Mardjono; Goehre, Felix; Hernesniemi, Juha (Frontiers in Surgery, 2022)
Given the rareness of available data, we performed a systematic review and meta-analysis on therapeutic strategies microsurgical resection and stereotactic radiosurgery (SRS) for brainstem cavernous malformations (BSCMs), and assessed mortality, permanent neurological deficits (PND), re-bleeding rate and patients requiring re-intervention in order to elucidate the benefits of each treatment modality. Preferred reporting items for systematic reviews and meta-analyses (PRISMA) were used for protocol development and manuscript preparation. After applying all inclusion and exclusion criteria, six remaining articles were included in the final manuscript pool. In total, this meta-analysis included 396 patients, among them 168 patients underwent microsurgical treatment and 228 underwent SRS. Findings of the present meta-analysis suggest that regarding the total group of patients, in terms of mortality, late re-bleeding rate, permanent neurological deficits and, there was no superiority of the one method over the other. Applying the leave-one-out method to our study suggests with low robust of the results for the bleeding rate and patients requiring re-intervention outcome factor that there wasn't statistical difference among the surgical and SRS treatment. Microsurgical treatment of BSCMs immediately eliminates the risk of re-hemorrhage, however, it requires complete excision of the lesion and it’s associated with a similar rate of permanent neurological deficits compared with SRS management. Apparently, SRS of BSCMs causes a marked reduction in the risk of re-bleeding 2 years after treatment, but when compared with the surgical treatment there wasn’t any remarkable different.